(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Numerous pharmacological effects of essential oils have been identified, one of which is their ability to deter insects and mosquitoes. The oil infused with Vetiveria zizanioides can reportedly treat insect bites and is antibacterial, astringent, and antifungal. Two different concentrations of mosquito repellent cream, 5% and 7.5%, were prepared and tested according to the American Society for Testing and Materials (ASTM) standard E951-83 by combining Vetiveria izanioides oil with two essential oils, clove oil and dill oil. A non-commercial mosquito repellent mixture has been tested on humans in a lab. All formulations were subjected to a sensory test to determine their consistency in terms of pH, clarity, homogeneity, gloss and spreadability, as well as colour, aroma, appearance and ease of use.